2013
DOI: 10.1105/tpc.113.113209
|View full text |Cite
|
Sign up to set email alerts
|

Control of Reproductive Floral Organ Identity Specification inArabidopsisby the C Function Regulator AGAMOUS  

Abstract: The floral organ identity factor AGAMOUS (AG) is a key regulator of Arabidopsis thaliana flower development, where it is involved in the formation of the reproductive floral organs as well as in the control of meristem determinacy. To obtain insights into how AG specifies organ fate, we determined the genes and processes acting downstream of this C function regulator during early flower development and distinguished between direct and indirect effects. To this end, we combined genome-wide localization studies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
213
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(221 citation statements)
references
References 90 publications
(178 reference statements)
8
213
0
Order By: Relevance
“…That this idea is at least in part correct for the floral organ identity factors is suggested by the expression of the corresponding genes in floral organs throughout most of their morphogenesis (Ó'Maoiléidigh et al, 2014a(Ó'Maoiléidigh et al, , 2014b. Also, the results of perturbation experiments, in which the floral organ identity genes were specifically disrupted or activated at different floral stages, showed that these master regulators have crucial functions in processes that take place during intermediate and late stages of flower development (Ito et al, 2007;Wuest et al, 2012;Ó'Maoiléidigh et al, 2013). However, the now prevailing view is that they largely act by controlling the expression of other genes with regulatory functions.…”
Section: Genes Acting Downstream Of the Floral Organ Identity Factorsmentioning
confidence: 89%
See 2 more Smart Citations
“…That this idea is at least in part correct for the floral organ identity factors is suggested by the expression of the corresponding genes in floral organs throughout most of their morphogenesis (Ó'Maoiléidigh et al, 2014a(Ó'Maoiléidigh et al, , 2014b. Also, the results of perturbation experiments, in which the floral organ identity genes were specifically disrupted or activated at different floral stages, showed that these master regulators have crucial functions in processes that take place during intermediate and late stages of flower development (Ito et al, 2007;Wuest et al, 2012;Ó'Maoiléidigh et al, 2013). However, the now prevailing view is that they largely act by controlling the expression of other genes with regulatory functions.…”
Section: Genes Acting Downstream Of the Floral Organ Identity Factorsmentioning
confidence: 89%
“…In particular, it is currently not known how the MADS protein complexes act at the mechanistic level. The different floral organ identity factors have similar albeit not identical DNA binding specificities , and the results of genomewide localization studies (Kaufmann et al, 2009(Kaufmann et al, , 2010Wuest et al, 2012;Ó'Maoiléidigh et al, 2013;Pajoro et al, 2014) showed that their global binding patterns exhibit large overlaps even in cases where two factors are not part of the same complex. At the same time, the sets of bona fide target genes, i.e.…”
Section: Floral Organ Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the described binding by BZR1 , BRs might also target PIF5 through direct binding by BES1 . Intriguingly, several transcription factors involved in the regulation of flowering (AP1, SVP, LFY, AG, and SEP3) have also been identified to bind PIFs (Kaufmann et al, 2009(Kaufmann et al, , 2010Moyroud et al, 2011;Tao et al, 2012;Gregis et al, 2013;ÓMaoiléidigh et al, 2013), suggesting a direct link to the reported flowering phenotype of pif mutants (Brock et al, 2010;Nozue et al, 2011;Kumar et al, 2012). Finally, binding by REV and AGL15 (Zheng et al, 2009;Brandt et al, 2012) suggests that some of the PIFs might be involved in leaf patterning or embryogenesis, a possibility that needs to be explored.…”
Section: Transcriptional Regulation Of the Pifsmentioning
confidence: 99%
“…Studies on the genome-wide binding of Arabidopsis MADS-domain proteins identify mechanisms underlying their role during flower development (Kaufmann et al, 2009Immink et al, 2012;Deng et al, 2011;Zheng et al, 2009;Wuest et al, 2012;Ó'Maoiléidigh et al, 2013;Gregis et al, 2013). These studies showed them to bind a multitude of downstream target genes and regulate their expression.…”
mentioning
confidence: 99%